Exports, imports and profitability: First evidence for manufacturing enterprises - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
This paper documents for the first time the relationship between profitability and three types of international trade activities - exports, imports and two-way trade. It uses unique new representative data for manufacturing enterprises from Germany, one of the leading actors on the world market for goods, that merge information from surveys performed by the Statistical Offices and administrative data collected by the Tax Authorities. Descriptive statistics and regression analysis (with and without controlling for unobserved firm heterogeneity and the role of outliers) point to the absence of any statistically significant and economically large effects of trade activities on profits. This demonstrates that any productivity advantages of trading firms are eaten up by extra costs related to selling and buying on foreign markets.
Keywords: F14; 330; exports; imports; profitability; Export; Import; Exportindustrie; Verarbeitendes Gewerbe; Rentabilität; Schätzung; Deutschland